2021
DOI: 10.1177/20420188211054690
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TPOAb-negative maternal subclinical hypothyroidism in early pregnancy on adverse pregnancy outcomes

Abstract: Purpose: To investigate the effect of subclinical hypothyroidism on pregnancy outcomes of women early in their pregnancy with different thyroid-stimulating hormone levels and thyroid peroxidase antibody–negative status and to explore reasonable thyroid-stimulating hormone levels for subclinical hypothyroidism in early pregnancy. Methods: A total of 2378 women early in their pregnancy were studied retrospectively. The baseline characteristics were collected from medical records. Pregnancy outcomes were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The median (IQR range) gestational age at which LT4 was started was 13 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) weeks, of whom 30.2% started treatment after 20 weeks of gestation. The starting dose of LT4 was 45.3 ± 16.3 ug / day.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The median (IQR range) gestational age at which LT4 was started was 13 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) weeks, of whom 30.2% started treatment after 20 weeks of gestation. The starting dose of LT4 was 45.3 ± 16.3 ug / day.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning PTB, we had too few cases in the SCH control group to perform a statistical analysis. Noteworthy is that in one of the two earlier mentioned Chinese studies on the impact of SCH, the 95% CI was large, indicating there were also few cases in that study (aOR 4.07 (95% CI: 1.26-13.14)) [10]. Moreover, in a systematic review and meta-analysis, the association between SCH and PTB was no longer signi cant after additional adjustment for TPOAb positivity either [9].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thyroid hormone is a key hormone that promotes growth and development, neural differentiation and maturation, and maintains the normal metabolism of the body. A previous study has shown that untreated SH during pregnancy seriously threatens the health of the mother and the fetus ( 1 ). The nucleotide-binding oligomerization domain-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is closely related to placental inflammation-related diseases, and its abnormal activation can lead to the activation of Caspase-1 and the maturation of gasdermin D (GSDMD), inducing pyroptosis and accompanying inflammatory response, disrupting the physiological balance of the maternal-fetal interface, and leading to the occurrence of various adverse pregnancy events ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%